Cost-Effectiveness of Aprepitant in Preventing Chemotherapy-Induced Nausea and Vomiting: A Systematic Review of Published Articles - Qiu, Tingting; Men, Peng; Sun, Tong; Zhai, Suodi (Frontiers in Public Health, 2021)
Abstract Objectives The aim of this systematic review is to assess the published cost-effectiveness analyses of aprepitane for patients with chemotherapy- induced nausea and vomiting (CINV). Methods A systematic literature searching was performed on PubMed, EMbase, the Cochrane Library，CNKI，WANFANG DATA and CBM database. The date of publication is up to January 2019. Two reviewers independently reviewed titles, abstracts, and articles sequentially to select studies for data abstraction based on the inclusion and exclusion criteria. Disagreements were resolved and reviewers reached consensus. The quality of included studies was assessed according to the 24-item checklist of the Consolidated Health Economic Evaluation Reporting Standards (CHEERS). The costs reported by the included studies were converted to US dollars via purchasing power parities(PPP) in the year 2019 using the CCEMG-EPPI-Certer Cost Converter. Results A total of 13 articles were included based on the inclusion cretiria for cost-effectiveness analysis (CEA) and cost-utility analysis (CUA). Twelve studies were rated as good quality based on the CHEERS checklist, one was rated as moderate quality. Eight studies compared aprepitant plus 5-hydroxytryptamine-3 receptor antagonist (5-HT3RA) and dexamethasone with standard regimen (5-HT3RA and dexamethasone), concluded that aprepitant plus standard regimen was a cost-effective strategy for preventing CINV. Only one study compared aprepitant plus 5-HT3RA with 5-HT3RA, concluded that the addition of aprepitant reduced the incidence of severe nausea and might also provide economic benefit in the overall management. Four studies compared aprepitant with other antiemetic drugs, concluded that aprepitant is a cost-effective strategy for preventing CINV compared with metoclopramide, however, NEPA and olanzapine are cost-effective compared with aprepitant. Conclusion This study is the first systematic evaluation of adding aprepitant to standard regimens for patients with CINV. Most economic evaluations of antiemetic medications is reported good quality. Adding aprepitant to standard regimens is found to be a cost-effective strategy for preventing CINV.